Manifestation of Integrated-Andragogic Islamic Education Based on Kitab Kuning in Indonesian Pesantren - Sufirmansyah, Sufirmansyah (Cendekia: Kependidikan dan Kemasyarakatan, 2023)
This article explores integrative-andragogic Islamic education based on the kitab kuning at Ma'had Aly Lirboyo Kediri. This study used a case study qualitative method. Data were collected through in-depth interviews, non-participant observation, and documentation. The data were then analyzed using a qualitative data analysis of the Miles-Huberman-Saldana interactive model, using Knowles' andragogy theory as an analytical tool. This article concludes that kitab kuning-based integrative Islamic education at Ma'had Aly Lirboyo Kediri is designed to develop students' competencies based on their potential and condition, using andragogic principles. A range of learning methods is utilized, such as expository, memorization, deliberation, and uswatun hasanah, to accommodate differences in age and understanding. The social environment is also used as a learning medium to optimize outcomes. Ma'had Aly Lirboyo implements an integrative kitab kuning-based Islamic education approach through classroom lectures, public lectures, and various extracurricular activities, including Ramadan safari, khidmah, LBM deliberations, bandongan book recitation, and community service. It confirms the successful application of andragogic principles in their learning methods.